(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Langhana is the treatment part of Ayurveda highly elaborated in its scientific approach. It is the form of Apatarpana generally opted for Santarpanajanya Vyadhi. Autophagy is relatively new and incidental finding of modern medicine which is currently researched on a very large scale for its anticipated outcomes in gerontology, autoimmune diseases as well as life style disorders. The results that are expected out of Langhana and the effects of autophagic mechanisms as presented today appear to be congruent although they are explained on different platforms with diverse terminology. Hence this is an attempt to put forth few complimentary aspects of both Langhana and autophagy which needs concrete scientific validation.